Biodiesel production from canola oil using a membrane reactor - Liu, Jie (University of Ottawa (Canada), 2005)
Biodiesel, a transesterified product of vegetable oil and animal fats, is considered as the most promising diesel fuel substitute because of its similar properties to petroleum-based diesel fuel. In this thesis, the miscibility of canola oil and fatty acid methyl esters (FAME or biodiesel) in methanol was determined. Results showed that FAME is miscible in pure methanol under a broad range of conditions. On the other hand, canola oil is not miscible in methanol under normal conditions. These findings led to the development of a two-phase membrane reactor to produce FAME from canola oil and methanol. The transesterification of canola oil was performed via both acid- or base-catalysis. The novel reactor enabled the separation of a FAME and methanol solution from canola oil/methanol/FAME mixtures. The two-phase membrane reactor was particularly useful in removing unreacted canola oil from the FAME product yielding high purity biodiesel. A kinetic study of the acid- and base-catalyzed transesterification of canola oil to FAME was carried out to investigate reaction rates under different temperatures and catalyst concentrations in the two-phase membrane reactor. Results showed that increases in temperature, acid concentration and feedstock (methanol/oil) flowrate significantly increased the conversion of oil to biodiesel. However, the base-catalyzed reaction resulted in the production of soaps and slight damage to the carbon membrane used in the reactor. The kinetics of the reaction were more sensitive to temperature at high acid concentration.
Keywords: Engineering, Chemical.; Energy.